Pengaruh Usahatani Durian Terhadap Ekonomi Keluarga Di Kecamatan Jaya Kabupaten Aceh Jaya - Syarifuddin Syarifuddin; Dedhi Yustendi; Irwan Safwadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to see the amount of durian farming household income, non durian farming income, total durian farmer household income and the contribution of durian farming income contribution to the total family income of durian farmers. The research methodology in this study is a survey method, simple random sampling technique, with a total sample of 55 durian farmer families. The results showed that the average durian farm income was Rp. 2,555,000, - per month. Non-farm average income ranges from Rp. 500,000, - to Rp. 5,000,000 per month, while the average total family income is Rp. 6,250,000, - per month. So that the durian farming income to the total family income is 40.88 percent. This means that the contribution of durian farming is included in the medium category.